Correlations of Through‐Plane Cell Voltage Losses, Imbalance of Electrolytes, and Energy Storage Efficiency of a Vanadium Redox Flow Battery. Issue 7 (7th March 2019) - Lim, Hyebin; Yi, Jung S.; Lee, Doohwan
Abstract: Correlations of the through‐plane voltage losses in the vanadium redox flow battery (VRFB), changes in the posolyte (positive electrolyte) and negolyte (negative electrolyte) conditions, energy storage capacity, and coulomb efficiency were investigated under an operando charge–discharge process. Collective and quantitative in situ studies with Ag/AgCl reference‐electrodes inserted into a VRFB single‐cell and the state of charge measuring external open‐circuit voltage half‐cells revealed that the overall performance of a VRFB is predominantly governed by (i) relatively high internal resistance of the anode half‐cell and (ii) conditions of the negolyte as the limiting electrolyte. The studies showed that the round‐trip coulomb efficiency, which is commonly used for VRFB performance analysis, has limitations in expressing the energy storage efficiency and capacity decay phenomena under a consecutive charge–discharge process. In situ and concurrent analysis of the internal cell overpotential and the electrolytes condition can provide quantitative information on the relative contributions of the coulombic round‐trip loss, concentration loss, vanadium crossover, and charge imbalance between the posolyte and negolyte for the overall efficiency and capacity decay phenomena. This operando analysis approach is highly effective for gaining an in‐depth and collective understanding of the complex phenomena taking place in the VRFB system. Abstract : Operando studies for collective analysis of the internal cell overpotentials and the electrolyte conditions allow for in‐depth understanding of the complex capacity decay phenomena and the performance of vanadium redox flow batteries.